2020
DOI: 10.7150/jca.38728
|View full text |Cite
|
Sign up to set email alerts
|

The LncRNA HOTAIRM1 Promotes Tamoxifen Resistance by Mediating HOXA1 Expression in ER+ Breast Cancer Cells

Abstract: Breast cancer is one of the most commonly diagnosed cancers in women worldwide. Approximately 40% of patients with breast cancer acquire endocrine resistance following therapy with tamoxifen. Many explanations for the development of endocrine resistance have been put forward, one of them being the dysregulation of long non-coding RNAs (lncRNAs). The lncRNA HOTAIRM1, known to be involved in myelopoiesis as well as transcriptional regulation of the HOXA genes in embryonic stem cells, is also expressed in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Among these ncRNAs, lncRNAs, as the promising molecular markers for forecasting drug resistance of breast cancer, are becoming new targets for treating breast cancer in the future. For example, LOC645166, lncRNA GAS5, and lncRNA H19 regulate adriamycin resistance in breast cancer cells [4,19,20], and lncRNA UCA1 and lncRNA NONHSAT141924 modulates paclitaxel resistance [21,22], while lncRNA HOTAIRM1 and BLACAT1 can induce tamoxifen resistance in ER + breast cancer cells [23,24]. However, all these lncRNAs were identi ed from breast cancer tissue or cell lines, which limits their utilities in the clinic as a dynamic monitoring biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Among these ncRNAs, lncRNAs, as the promising molecular markers for forecasting drug resistance of breast cancer, are becoming new targets for treating breast cancer in the future. For example, LOC645166, lncRNA GAS5, and lncRNA H19 regulate adriamycin resistance in breast cancer cells [4,19,20], and lncRNA UCA1 and lncRNA NONHSAT141924 modulates paclitaxel resistance [21,22], while lncRNA HOTAIRM1 and BLACAT1 can induce tamoxifen resistance in ER + breast cancer cells [23,24]. However, all these lncRNAs were identi ed from breast cancer tissue or cell lines, which limits their utilities in the clinic as a dynamic monitoring biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that due to increased phosphorylation of EZH2, EZH2 protein levels did not increase as they did with short-term genistein exposure. Recent study has shown that EZH2 was evidently less enriched in TAMR cells [54]. Study has found that that low H3K27me3 level were signi cantly associated with aromatase inhibitor resistance [25].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that lncRNAs as ceRNAs have profound implication in controlling endocrine response of BC. In addition, a newly published study has demonstrated that lncRNA HOTAIRM1 promotes acquired tamoxifen resistance in BC by interacting with EZH2, thus preventing the PRC2 complex-mediated H3K27me3 of the putative HOXA1 promoter 69 . This study indicates that HOTAIRM1 is a promising therapeutic target for BC patients with tamoxifen resistance.…”
Section: Lncrnas-mediated Bc Resistance In Different Clinical Scenarimentioning
confidence: 99%